BACK TO NATURE”: EMERGING FAITH IN REVITALISING POWER OF NATURE IN CONTEMPORARY INDIAN ENGLISH WOMEN POETRY - Bajaj, Rashmi; Batra, Aparna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the increased urbanization and industrialisation in the last few decades, the physical and mental space for the world of Nature has considerately shrunk in Life and Literature. Homosapiens and their multiple concerns have come centrestage to dominate all discourses ,with other entities relegated to the background. However, Nature has continued to occupy a significant place in women-writing across globe. The poetic corpus of Indian English women poets contains beautiful descriptions of the natural world, portrayal of close human-nature interface and also expression of some deep metaphysical and esoteric human experiences vis-à-vis Nature as the poets go beyond the mere outer manifestations of nature. This paper takes up an in-depth perusal of various dimensions of Human-Nature interface in the poetry of the contemporary poets. It also explores the distinctive aspects of their Nature-related vision and philosophy as these poets strive to connect with nature in their quest to strike roots in our route-less and rootless tempestuous Times.